Bibliometric Analysis of Integrated Pest Management in Sustainable Agriculture - Judijanto, Loso; Sutiharni, Sutiharni; Angrianto , Rusdi; Ayuningtias, Nandini; Nurlailah , Nurlailah (Westscience Press, 2025)
Integrated Pest Management (IPM) has emerged as a sustainable alternative to conventional pest control methods, emphasizing the integration of biological, cultural, mechanical, and chemical approaches. This study conducts a bibliometric analysis of IPM research using data exclusively from the Scopus database and analyzed through VOSviewer. The findings reveal a significant increase in IPM-related publications over the past two decades, indicating growing global interest in sustainable pest management. Key research themes identified include pesticide reduction, biological control, policy frameworks, and technological advancements such as artificial intelligence for pest monitoring. The study also highlights the dominance of developed countries, particularly the United States, United Kingdom, and China, in IPM research, while collaboration between developed and developing nations remains limited. Major challenges to IPM adoption include economic constraints, lack of technical knowledge, and regulatory barriers. Future research should focus on enhancing global collaboration, improving accessibility to biopesticides and digital technologies, and strengthening farmer education and policy support. This study provides valuable insights into the evolution of IPM research and its role in promoting sustainable agriculture.